Piepkorn type of osteochondrodysplasia: Defining the severe end of FLNB‐related skeletal disorders in three fetuses and a 106‐year‐old exhibit. Issue 7 (23rd May 2018) - Rehder, Helga; Laccone, Franco; Kircher, Susanne G.; Schild, Ralf L.; Rapp, Christiane; Bald, Rainer; Schulze, Bernt; Behunova, Jana; Neesen, Juergen; Schoner, Katharina
Abstract : The Piepkorn type of lethal osteochondrodysplasia (POCD) is a rare and lethal dwarfing condition. Four cases have been reported to date. The characteristic features are distinctly shortened "flipper‐like" limbs, polysyndactyly, excessive underossification, especially of the limb bones and vertebrae, and large (giant) chondrocytes in the cartilaginous bone primordia. These characteristics allowed the diagnosis of Piepkorn type of osteochondrodysplasia in four new cases, three fetuses of 15 to 22 weeks and one 106‐year‐old museum exhibit. Piepkorn type of osteochondrodysplasia has been assigned to the giant cell chondrodysplasias such as atelosteogenesis type 1 (AO1) and boomerang dysplasia (BD). Analysis of the Filamin B gene in 3p14.3, which is associated with these disorders, allowed the identification of the first FLNB mutations in Piepkorn type of osteochondrodysplasia. The heterozygous missense mutations, found in the three fetuses, were located in exons 28 and 29, encoding the immunoglobulin‐like repeat region R15, one of three mutational hot spots in dominant FLNB ‐related skeletal disorders. Direct preparations and alcian blue staining revealed single upper and lower arm and leg bone primordia, preaxial oligodactyly, and polysyndactyly with complete fusion and doubling of the middle and end phalanges II–V to produce eight distal finger rays. Considering the unique clinical features and the extent of underossification, Piepkorn type of osteochondrodysplasia can be regarded as a distinct entity within the AO1‐BD‐POCD continuum.